Mild reductive cleavage of tryptophan and histidine side-chain protecting groups - Maia, Hernâni Lopes Silva (2001)
The activation potentials of the p-toluenesulfonyl and benzoyl groups as determined by cyclic voltammetry when they are Linked to indole or imidazole are less negative than when these groups are linked to aliphatic amines. This makes them most suitable for side-chain protection of tryptophan and histidine, as it allows mild selective cleavage not only by controlled-potential electrolysis but also by chemical reduction using either magnesium in anhydrous methanol or mercury-activated aluminum.